The last thing Mary saw [videorecording (DVD)] - Vitaletti, Edoardo; Scott, Stefanie, 1996-; Fuhrman, Isabelle, 1997-; Roberts, Judith Anna; Culkin, Rory (RLJ Entertainment, 2022)
Young Mary, who hides a romantic relationship with the housemaid, was raised in a repressively religious household. Her family, who believe they are acting on God's behalf, view the girls' relationship as an abomination to be dealt with as severely as possible. The couple attempts to carry on in secret, but someone is always watching, and the threat to pay for their sins builds. But after the arrival of an enigmatic stranger, the tension increases, and it becomes clear that great and evil forces are at work.